Literary Testaments: The Difficult Art of Mediation - Namora, Ricardo (MATLIT: Materialities of Literature, 2014)
Review of Jerónimo Pizarro, La Mediación Editorial – Sobre la Vida Póstuma de lo Escrito. Madrid: Iberoamericana Editorial Vervuert, 2012, 304 pp. ISBN: 978-84-8489-706-4.